Lipid nanoparticles for the posterior eye segment - Bonilla, Lorena (2022)
This review highlights the application of lipid nanoparticles (Solid Lipid Nanoparticles, Nanostructured Lipid Carriers, or Lipid Drug Conjugates) as effective drug carriers for pathologies affecting the posterior ocular segment. Eye anatomy and the most relevant diseases affecting the posterior segment will be summarized. Moreover, preparation methods and different types and subtypes of lipid nanoparticles will also be reviewed. Lipid nanoparticles used as carriers to deliver drugs to the posterior eye segment as well as their administration routes, pharmaceutical forms and ocular distribution will be discussed emphasizing the different targeting strategies most recently employed for ocular drug delivery.